HVDC transmission system using multilevel power converters based on dual three-phase two-level inverters. (February 2015) - Fernão Pires, V.; Fialho, João; Fernando Silva, J.
Highlights: A HVDC transmission system based on a multilevel structure with two DC links. Multilevel AC voltage waveforms from standard three-phase converters connected to a three-phase open winding transformer. The total power transmitted in the DC link is shared by the two three-phase converters. The control algorithm is based on sliding mode control theory coupled to a space vector modulator. The proposed HVDC system has been tested by numerical simulations. Abstract: Multilevel converters are now an attractive solution for high-voltage direct-current (HVDC) electrical energy transmission systems. Unlike the well-known two-level voltage source converters, multilevel converters use 3 or more voltage levels or steps per leg to modulate the ac voltages, decreasing voltage distortion and reducing electromagnetic interference. This work presents a HVDC transmission system based on a new multilevel structure using a dual two-level converter topology. This structure attains multilevel operation and advantages using two well known three-phase voltage source two-level inverters connected to one three-phase open windings transformer. The proposed dual converter structure has two independent dc links allowing each inverter to process half of the total power. This arrangement is fitted with a control system designed to control the active and reactive power towards their specific set point values, while balancing the voltages of the two dc link capacitors in real time. Obtained results show the effectiveness of the proposed HVDC transmission system.